Enhancing cysteine content in yogurt with addition of whey protein isolate and its sensory evaluation - Bala, Soumya (Kansas State University, 2013)
Milk proteins are excellent sources of sulfur-containing amino acids methionine and cysteine, in particular whey proteins. Cysteine is synthesized from methionine by γ-cystathionase. However, cysteine has to be included in the diets of certain subpopulations due to diminished γ-cystathionase activity. Cysteine, a heat- liable amino acid, may lose bioavailability during thermal processing. The objective of this research was to enhance cysteine content in yogurt while maintaining its quality. First, yogurt mixes were formulated to a total solids content of 12.5% with nonfat dry milk (NDM) (N) or a combination of NDM (10%) and whey protein isolate (WPI) (2.5%) (W), and processed at 70°C (20 min) (70) or 90°C (7 min) (90). Yogurt was prepared and maintained at 4oC for 60 days. Three replications were performed and data were analyzed using SAS®. The W mixes had 65%, 32% and 190% more cysteine, true protein and whey protein contents respectively, compared to N mixes prior to processing. However in day 1 yogurt, the highest cysteine content (398.3 mg/L) was found in the W70 yogurt and its gel quality was comparable to the N90 yogurt except for firmness. During a 60 day storage period the W70 and N90 were similar in gel quality except for firmness. Secondly, a hedonic test was done on the W70 (HC) and N90 (LC) yogurts which had been reformulated to contain sugar and vanillin. One replication was performed and data were analyzed using SAS®. The LC and HC yogurts did not vary in liking of flavor (6.1), aftertaste (6.1) and overall acceptability (6.3) corresponding to the words of “like slightly” when compared. However, the appearance of the LC yogurt was liked more than the HC yogurt (6.7 vs. 6.1) whereas the thickness of HC yogurt was liked more than the LC yogurt (6.4 vs. 5.8). These results suggest that addition of WPI along with lower process treatment resulted in yogurt with enhanced cysteine; however, further studies may be needed to optimize the WPI addition to improve the visual characteristics of the yogurt for consumer acceptance.
Keywords: Cysteine; Whey protein isolate; Yogurt; Food Science (0359)